An evaluation of performance characteristics in high-level youth soccer players - McFadden, B.; Arent, M.; Chandler, A.; Bozzini, B.; Cintineo, H.; Walker, A.; Mackowski, N.; Hofacker, M.; Arent, S. (The Journal of Strength and Conditioning Research, 2021)
Youth athletes often specialize in sport at an early age. Identifying and selecting talent for a given sport commonly begins in childhood, despite maturation and development occurring at different rates. Purpose: To determine performance and body composition (BC) characteristics of high-level female youth soccer players according to chronological age groups. Methods: One-hundred nine high-level female soccer athletes (Age = 14.7 ± 1.5 years; Weight = 56.3 ± 7.7 kg; Height = 164.4 ± 6.1 cm) from the same soccer academy participated in assessments. Athletes arrived at the laboratory for testing >2 hours fasted, >4-hours abstention from caffeine, and having refrained from exercise >24 hours. BC was assessed via air displacement plethysmography to determine percent body fat (%BF) and fat free mass (FFM). Maximal counter-movement vertical jump (CMJ) height was assessed via contact mat. Aerobic capacity (VO2max) and ventilatory threshold (VT) were assessed by indirect calorimetry during a maximal graded-exercise test on a treadmill using the Bruce protocol. Athletes were stratified into groups based on age: G1 (12-13 years; n = 27; Mage = 12.9 ± 0.3 years), G2 (14-15 years; n = 56; Mage = 14.5 ± 0.5 years), and G3 (16-17; n = 26; Mage = 16.9 ± 0.7 years). MANOVAs with univariate follow-ups were conducted and significance set at P <= 0.05. Descriptive statistics are presented as Mean ± SD and Meandiff ± SE. Results: G1 averages were: FFM = 43.0 ± 6.4 kg; %BF = 16.5 ± 4.0%; CMJ = 46.5 ± 4.2 cm; VO2max = 52.8 ± 4.1 ml/kg/min; VT = 77.6 ± 5.1%. G2 averages were: FFM = 45.6 ± 4.2 kg; %BF = 18.6 ± 4.1%; CMJ = 46.5 ± 5.1 cm VO2max = 53.4 ± 4.9 ml/kg/min; VT = 79.7 ± 4.9%. G3 averages were: FFM = 49.5 ± 4.6 kg; %BF = 18.7 ± 4.0%; CMJ = 48.7 ± 4.8 cm; VO2max = 50.2 ± 4.6 ml/kg/min; VT = 80.3 ± 5.3%. Comparing groups, FFM was greater in G3 compared to G1 (Mdiff = 6.5 ± 1.4 kg; P = 0.001) and G2 (Mdiff = 3.9 ± 1.2 kg; P = 0.001). FFM in G2 was greater than G1 (Mdiff = 2.6 ± 1.2 kg; P = 0.03). %BF was greater than G1 in both G3 (Mdiff = 2.3 ± 1.1%; P = 0.04) and G2 (Mdiff = 2.1 ± 0.9%; P = 0.03). No differences in %BF were seen from G2 to G3. VO2max was greater in G1 than G3 (Mdiff = 2.8 ± 1.3 ml/kg/min; P = 0.04) and G2 than G3 (Mdiff = 3.4 ± 1.1 ml/kg/min; P = 0.01). No differences in VO2max were seen between G1 and G2. VT was not different across groups (P > 0.05). CMJ was greater in G3 compared to G2 (Mdiff = 2.2 ± 1.1 cm; P = 0.05) while no other differences in CMJ were found (P > 0.05). Conclusions: Youth athletes change physically and physiologically during different levels of sport development. Specifically, greater FFM, %BF, CMJ, and lower VO2max were found in the oldest groups which may be attributed to changes in maturation or training status. Systematic testing allows for the comparison to normative data and the assessment of an athlete's development. Practical Application: Long-term athlete development focuses on maximizing individual potential. Considerations must be made for training youth athletes as physiological components are continually developed throughout adolescence. Measuring physiological attributes during a training cycle using performance tests can help track player progress and identify strengths and weaknesses in order to optimize performance. As the selection to high-level teams occurs periodically during a youth athlete's career, systematic testing can inform training practices and ensure athletes are ready to compete at the next level. Additionally, determining fitness characteristics of high-level youth athletes by age group may better serve to guide strength and conditioning prescriptions.